Analisis Peran Orang Tua Dalam Peningkatan Literasi Anak Usia Sekolah Dasar - Mai Sri Lena; Sahrun Nisa; Silvi Wardahtun Aisyah; Rizka Khairani (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
This journal aims to analyze the role of parents in increasing the literacy of elementary school age students. Parents are someone who is very close to the child. Parents are tasked with providing important stimulations in an effort to improve the literacy abilities of elementary school-age children. Many literacy movements have been carried out in schools to encourage elementary school-age children to like reading, but actually the key to reading for children depends on the active role of parents. The results of the data analysis show that there are 6 types of parental involvement which include involvement in the form of parenting, communication, volunteering, empowering learning at home, collaboration with the community and decision making. Although parental involvement has its own challenges, it has been proven to help increase not only student literacy, in reading and writing, but also literacy in other areas that reflect real-world literacy. It is hoped that the results of this research can inspire related parties on how to empower the role of parents to increase student literacy.